Manajemen Perpustakaan Berbasis Digital Dalam Meningkatkan Mutu Layanan Di U.P.A Perpustakaan Universitas Tadulako - Nurhayati Nurhayati; Daswati Daswati; Nuraisyah Nuraisyah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The aim of this research is to find out what is the digital-based library service management system in the Academic Support Unit (U.P.A) Tadulako University Library? The types of data used are primary data and secondary data. Data collection techniques are carried out through observation, interviews and documentation. The informants in this research were 3 (three) people. The data analysis used is the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The theory used is Wu and Chen's theory regarding digital library service management. The research results show that digital library management at UPA Libraries has implemented all three aspects of digital library service management including digital catalog aspects, automatic lending systems, and access to electronic databases and e-journals. The conclusion of this research is that the Tadulako University Library UPA has implemented digital library service management.